Fatigue analysis of high performance race engines. (May 2020) - Rølvåg, T.; Haugen, B.; Bella, M.; Berto, F.
Highlights: A FEM based multidiscipline dynamic simulation tool for fatigue testing is developed. Strain coat elements (virtual brittle lacquer) is developed for hot spot identification. Strain rosettes are developed for fast calculation of strain histories of large FEMs. The simulation tool is successfully benchmarked on a drag race engine. Abstract: This paper presents a multidiscipline dynamic simulation tool for fatigue testing. A non-linear finite element formulation embedding control system modeling is augmented to include fatigue analysis based on a mathematical representation of virtual brittle lacquer and strain rosettes. A new efficient method for rosette strain calculations based on super node displacements are applied and presented. These features are used to predict the hot spots and durability of a high performance race engine. Real physical testing is performed to capture all engine properties influencing the crank shaft stress distribution. The results predict the most critical failure modes during racing applications as well as the life in terms of drag laps before failure.